Molecular characterization and expression analyses of toll like receptor-5 induced by Vibrio parahaemolyticus antigens in Pacific red snapper. Issue 68 (September 2017) - Reyes-Becerril, Martha; Alamillo, Erika; Rosales-Mendoza, Sergio; Ascencio, Felipe; Esteban, M. Angeles; Angulo, Carlos
Abstract: Toll-like receptor 5 (TLR5) is a member of TLRs family responsible for the bacterial flagellin recognition in vertebrates. Herein, the TLR5M gene structure of Pacific red snapper ( Lutjanus peru ) was characterized. The full-length cDNA of Lp TLR5M comprises an open reading frame (ORF) of 2715 bp, encoding a polypeptide of 904 amino acids including 9 LRRs (residues 119–562) and one LRR-CT domain (residues 593–646) at the extracellular region, and a TIR domain (residues 710–904) in the cytoplasmic region. The amino acid sequence in L. peru TLR5 showed high identity (66–69%) with TLR5 from Paralichthys olivaceus and Scophthalmus maximus . Quantitative real-time PCR (qPCR) analysis demonstrated the constitutive expression of Lp TLR5M mRNA in all the examined tissues, with higher levels in intestine, liver, and head-kidney. Furthermore, expression of Lp TLR5M and five cytokine genes was also investigated 24 h and one week post-stimulation in fish intraperitoneally injected with ToxA, live V. parahaemolyticus (Vp) or V. parahaemolyticus Lysate antigens. TLR5M was significantly induced in fish infected with Vp. The pro-inflammatory cytokines IL-6, IL8 and IL-12 were significantly up-regulated in head-kidney in fish stimulated with Vp, while in intestine upregulation was observed following ToxA or Lysate injection. In contrast, IL-17 mRNA was significantly up-regulated in the intestine from fish infected with live Vp at 24 h post-injection. The results indicate that Lysate and Vp antigens can induce an immune response via TLR5M and that cytokines have an important role in the defense mechanisms against V. parahaemolyticus . Highlights: TLR5 gene functional architecture from Lutjanus peru was characterized in silico . TLR5 gene is highly expressed in intestine, liver and head-kidney. TLR5 and interleukine expressions were induced in head-kidney and intestine following bacterial infection. Recombinant ToxA injection upregulated IL-17 in head-kidney and IL-8 in intestine. Lysate administration upregulated IL-10 in head-kidney and IL-12 in intestine.